Drosophila eye size is determined by Innexin 2-dependent Decapentaplegic signalling. - Richard, M.; Hoch, M. (Developmental Biology, 2015)
Organogenesis relies on specific genetic and molecular programmes, which orchestrate growth and cellular differentiation over developmental time. This is particularly important during Drosophila eye development in which cell-cell inductive events and long-range signalling have to be integrated to regulate proper cell proliferation, differentiation and morphogenesis. How these processes are coordinated is still not very well understood. Here we identify the gap junction protein Innexin2 (Inx2) as an important regulator of eye development. Depleting inx2 during eye development reduces eye size whereas elevating inx2 levels increases eye size. Loss- and gain-of-function experiments demonstrate that inx2 is required functionally in larval eye disc cells where it localises apico-laterally. inx2 regulates disc cell proliferation as well as morphogenetic furrow movement and as a result the amount of differentiated photoreceptors. inx2 interacts genetically with the Dpp pathway and we find that proper activation of the Dpp pathway transducer Mad at the furrow and expression of Dpp receptors Thickveins and Punt in the anterior disc compartment require inx2. We further show that inx2 is required for the transcriptional activation of dpp and punt in the eye disc. Our results highlight the crucial role of gap junction proteins in regulating morphogen-dependent organ size determination.